J Liver 2019
DOI: 10.35248/2167-0889.19.8.236
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis Conventional and Molecular Imaging Diagnosis Update

Abstract: Liver fibrosis is a serious, life-threatening disease with high morbidity and mortality that result from diverse causes. Liver biopsy, considered the “gold standard” to diagnose, grade, and stage liver fibrosis, has limitations in terms of invasiveness, cost, sampling variability, inter-observer variability, and the dynamic process of fibrosis. Compelling evidence has demonstrated that all stages of fibrosis are reversible if the injury is removed. There is a clear need for safe, effective, and reliable non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 117 publications
(112 reference statements)
0
25
0
Order By: Relevance
“…13,41,42 Recent advances in molecular and targeted MR imaging studies of small molecules that bind to fibrillary collagen or other ECM proteins are promising noninvasive approaches in the direct detection and quantification of liver fibrosis that would help overcome some of these limitations. [43][44][45]…”
Section: Noninvasive Tests For Fibrosis Assess-mentmentioning
confidence: 99%
See 1 more Smart Citation
“…13,41,42 Recent advances in molecular and targeted MR imaging studies of small molecules that bind to fibrillary collagen or other ECM proteins are promising noninvasive approaches in the direct detection and quantification of liver fibrosis that would help overcome some of these limitations. [43][44][45]…”
Section: Noninvasive Tests For Fibrosis Assess-mentmentioning
confidence: 99%
“…These data are essential in tracking disease progression, prognostication, identifying patients who are most likely to benefit from any therapeutic intervention, and assessing the efficacy of antifibrotic drugs [ 13 , 41 , 42 ]. Recent advances in molecular and targeted MR imaging studies of small molecules that bind to fibrillary collagen or other ECM proteins are promising noninvasive approaches in the direct detection and quantification of liver fibrosis that would help overcome some of these limitations [ 43 - 45 ].…”
Section: Noninvasive Tests For Fibrosis Assessmentmentioning
confidence: 99%
“…Angulo et al [ 34 ] suggested that by applying the NAFLD fibrosis score, a liver biopsy to determine the severity of fibrosis can be avoided in approximately 75% of patients with NAFLD. Conventional ultrasonography (US) is the most common technique used for the assessment of morphological and structural changes to the liver in clinical settings [ 35 , 36 ]. Although conventional US is useful in evaluating cirrhosis, it has a lower sensitivity for diagnosing early stages of liver fibrosis [ 37 , 38 ].…”
Section: Assessment Of Liver Fibrosis In Nafldmentioning
confidence: 99%
“…Unfortunately, a high cost and the complexity of scanning sequences of MRE restrict its use in comparison with USE. [ 41 ] Other imaging methods are helpful in diagnosing and assessing hepatic fibrosis, but they have less applications than elastographs, including diffusion weighted imaging (DWI), [ 42 ] magnetic resonance imaging (MRI) T 1 and T 2 mapping, [ 43 ] MRI perfusion (PWI), [ 44 ] texture analysis (TA), [ 45 ] and susceptibility weighted imaging (SWI). [ 46 ] Indeed, some studies have suggested that these imaging methods, especially MRE, could reach an equivalent or even better efficacy than liver biopsy and they could be used to replace the invasive diagnostic method.…”
Section: Current Diagnosis Methods For Hepatic Fibrosismentioning
confidence: 99%